2014
DOI: 10.2147/lra.s60966
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous patient-controlled fentanyl with and without transversus abdominis plane block in cirrhotic patients post liver resection

Abstract: BackgroundCoagulation changes can complicate liver resection, particularly in patients with cirrhosis. The aim of this prospective hospital-based comparative study was to compare the postoperative analgesic efficacy of intravenous fentanyl patient-controlled analgesia (IVPCA) with and without transversus abdominis plane (TAP) block.MethodsFifty patients with Child’s A cirrhosis undergoing liver resection were randomly divided into two groups for postoperative analgesia, ie, an IVPCA group receiving a 10 μg/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Postoperative variables included NRS scores, cumulative sufentanil consumption, the incidence of PONV. Ramsay Sedation Scale scores [ 11 ] collected 5 min after extubation, and 2 h, 4 h, 12 h and 24 h after the operation was evaluated as: [ 1 ] the patient is anxious and agitated or restless, or both; [ 2 ] the patient is co-operative, oriented and tranquil; [ 3 ] the patient responds to commands only; [ 4 ] the patient exhibits brisk response to light glabellar tap or loud auditory stimulus; [ 5 ] the patient exhibits a sluggish response to light glabellar tap or loud auditory stimulus; and [ 6 ] the patient exhibits no response.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative variables included NRS scores, cumulative sufentanil consumption, the incidence of PONV. Ramsay Sedation Scale scores [ 11 ] collected 5 min after extubation, and 2 h, 4 h, 12 h and 24 h after the operation was evaluated as: [ 1 ] the patient is anxious and agitated or restless, or both; [ 2 ] the patient is co-operative, oriented and tranquil; [ 3 ] the patient responds to commands only; [ 4 ] the patient exhibits brisk response to light glabellar tap or loud auditory stimulus; [ 5 ] the patient exhibits a sluggish response to light glabellar tap or loud auditory stimulus; and [ 6 ] the patient exhibits no response.…”
Section: Methodsmentioning
confidence: 99%
“…Epidural analgesia, another routinely used analgesic technique, offers equivalent or superior pain scores when compared toconventional systemic opioids. However, its utilizationis limited by perioperative coagulation dysfunction, which is typical in the patients for liver surgery and subsequent catastrophic neurologic injuries resulting from epidural haematoma [ 3 5 ]. In addition, epidural analgesia is independently associated with an increased use of blood transfusions and a longer hospital stay [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In laparotomy, RSB has been shown to significantly reduce morphine use (0.7 mg vs. 6.4 mg) [8] and pain scores (VAS score at 6 h, 2 vs. 3) when compared with placebo [9]. These studies either used a single-shot technique [8][9][10][11], combined with TAP block [12,13], or with continuous catheters [13, 14•]. A retrospective case-control study suggested the analgesic efficacy of RSB for open pyloromyotomy in infants [15].…”
Section: Laparotomymentioning
confidence: 99%
“…Recently, Melloul et al published guidelines to enhanced recovery after liver surgery and concluded that no evidence exists to prefer epidural, and wound infiltration and intrathecal opioids are good alternatives when combined with multimodal analgesia. [ 6 ] Transversus abdominis plane (TAP) block can help provide analgesia,[ 7 8 ] but the safety of injecting local anesthetics in this plane was questioned. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%